2013
DOI: 10.1097/igc.0b013e318280f3e0
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Human Papillomavirus in Ovarian Cancer: A Systematic Review

Abstract: We found a high prevalence of HPV-positive DNA in ovarian cancer cases, but the role of HPV in ovarian cancer remains inconclusive. Further studies are needed to control case to answer this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 25 publications
(24 reference statements)
3
35
0
1
Order By: Relevance
“…The etiology of OCa is multifactorial; the main causes are genetic, environmental, and sexual behavior and HPV which is the main pathogen that leads to OCa (21). Previous studies report different ranges of HPV prevalence in OCa, even some studies were unable to detect HPV in OCa (21)(22)(23)(24). A wide range of study results do not demonstrate the exact prevalence of HPV and this could be because of different study conditions like the type of histopathology sampling, sample transferring and storage condition, the type of method that is used for HPV detection, molecular technique conditions, the time of the study, OCa stage, and patient conditions like age, race and ethnicity, sexual behavior, and the genetics.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The etiology of OCa is multifactorial; the main causes are genetic, environmental, and sexual behavior and HPV which is the main pathogen that leads to OCa (21). Previous studies report different ranges of HPV prevalence in OCa, even some studies were unable to detect HPV in OCa (21)(22)(23)(24). A wide range of study results do not demonstrate the exact prevalence of HPV and this could be because of different study conditions like the type of histopathology sampling, sample transferring and storage condition, the type of method that is used for HPV detection, molecular technique conditions, the time of the study, OCa stage, and patient conditions like age, race and ethnicity, sexual behavior, and the genetics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they showed that the prevalence of HPV-16 increased during 2000 to 2005 and started to decrease after 2006 in OCa patients (24). The highest prevalence of HPV in OCa patients was 26.9% -35.9%, all of whom were from China (24,29,30). Our results, in comparison with previous studies, showed that the prevalence of HPV-16 in OCa patients has increased in our country; it, of course, could be predicted as the highest prevalence of HPV is in Asia among the continents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations